I Scratch and Sense But Can I Program?: An Investigation of Learning with a Block Based Programming Language - Simpkins, N K (International journal of information and communication technology education, 2014)
This article reports an investigation into undergraduate student experiences and views of a visual or ‘blocks' based programming language and its environment. An additional and central aspect of this enquiry is to substantiate the perceived degree of transferability of programming skills learnt within the visual environment to a typical mainstream textual language. Undergraduate students were given programming activities and examples covering four basic programming concepts based on the Sense programming language which is intended to simplify programming. Sense programming statements are represented by blocks which only fit together in ways that produce a meaningful syntactic outcome, which may lower the cognitive barrier to learning. Students were also presented with concepts represented using an equivalent textual construct and asked to consider their understanding of these based on the graphical cases. They were finally asked to complete a short online survey. This paper presents the programming activities, the survey and an analysis of the results.